Enhancing the Properties of Steel Fiber Self-Compacting NaOH-Based Geopolymer Concrete with the Addition of Metakaolin - Samy Elbialy; Ahmed A. El-Latief; Hebah M. Al-Jabali; Hebatallah A. Elsayed; Shymaa M. M. Shawky (Civil Engineering Journal, 2024)
There is a demand for innovative construction materials that offer enhanced mechanical characteristics while also being cost-effective and environmentally friendly. This paper examines the fresh properties and mechanical properties of geopolymerized self-compacting concrete (SCC) reinforced with steel fibers, containing 0–100% metakaolin (MK) by mass, as an eco-friendly substitute for Portland cement. SCC combinations included one or more waste cementitious materials (WCMs), such as metakaolin (MK), NaOH as an alkaline activity, and double-hook end steel fibers. For every NaOH geopolymer SCC blend, the mechanical characteristics (compressive strength, splitting tensile strength, flexural strength), as well as the new properties (lump flow, V-Funnel, L-box test), were read up. The findings indicate that combining metakaolin and steel fibers reduces the flowability of NaOH-based geopolymer SCC. On the other hand, incorporating MK and steel fibers enhances the compressive and flexural strength of NaOH-based geopolymer SCC with 25% metakaolin and 0.3% steel fiber. In contrast to the fiber-reinforced NaOH-based geopolymer SCC samples, which could transfer a sizable load even when the crack mouth opening deflection rose at flexural strength, the fiber-free SCC samples showed a brittle and abrupt fracture. The findings showed that the addition of NaOH as an alkaline activator, MK, and steel fiber had a negative impact on the fresh state properties; however, their combined use greatly enhanced the bond strength and flexural performance of the NaOH geopolymer SCC specimens. Doi: 10.28991/CEJ-2024-010-07-011 Full Text: PDF